Increasing the Growth and Yield of Soybean Genotype in Dryland by Applying Vesicular Arbuscular Mycorrhiza (VAM) and Tricho-compost - Bibiana Rini Widiati; Muh Izzdin Idrus; Andi Nur Imran (UNIVERSITY OF LAMPUNG, 2024)
This research aimed to examine the increase in growth and yield of soybean (Glycine max (L.) Merr) genotypes in the application of Vesicular Arbuscular Mycorrhizae (VAM) and tricho-compost in dryland. This research was conducted in the form of an experiment using a Split plot design was composed: all treatments were given NPK fertilizer at a dose of 50% of the recommended dose and 5 g of mycorrhizae (Glomus sp. + Gigaspora sp. + Acaulospora sp.). The main plot (MP) had six genotypes (G). The sub-plot (SP) was mycorrhizae +tricho-compost (T): mycorrhizae +without tricho-compost (t0), mycorrhizae +tricho-compost 50 g plant-1 (t1 ), and mycorrhizae +2tricho-compost 100 g plant-1 (t2 ). The results showed that soybean genotypes gM50Gy, gO50Gy, and gT50Gy have the stability of agronomic characteristics on the shoot dry weight, root dry weight, and soybean dry weight in the adaptation test in dryland. The treatment of tricho-compost 100 g ton-1 had the highest increased shoot dry weight, root dry weight, percentage of mycorrhizal infection, and Nitrogen (N), Phosphorus (P), and Potassium (K) uptake. The interaction of gT50Gyt2 ; gO50Gyt2 and gTt2 resulted in higher root dry weight and N, P, and K uptake than gM50Gyt2; gMt2; gOt2.